A REVIEW OF THEORETICAL AND PRACTICAL ASPECTS OF THE DEVELOPMENT OF UKRAINE'S CREATIVE ECONOMY - Фоменко, Валерій; Чала, Вероніка (SWorldJournal, 2025)
The article investigates the development of Ukraine's creative economy amid modern global challenges, including war, digitalization, and European integration. A terminological analysis of key approaches to defining the "creative economy" is conducted, ba